The effectiveness of an m-Health intervention on the sexual and reproductive health of in-school adolescents: a cluster randomized controlled trial in Nigeria - Oluwatosin Wuraola Akande; Moise Muzigaba; Ehimario Uche Igumbor; Kelly Elimian; Oladimeji Akeem Bolarinwa; Omotosho Ibraheem Musa; Tanimola Makanjuola Akande (Reproductive Health, 2024)
Abstract Background The implementation of the country-wide comprehensive sexuality education (CSE) curriculum among in-school adolescents remains abysmally low and mHealth-based interventions are promising. We assessed the effect of a mHealth-based CSE on the sexual and reproductive health (SRH) knowledge, attitude and behaviour of in-school adolescents in Ilorin, northcentral Nigeria. Methods Using schools as clusters, 1280 in-school adolescents were randomised into intervention and control groups. Data was collected at baseline (T0), immediately after the intervention (T1) and 3 months afterwards (T2) on SRH knowledge, attitude and practice of risky sexual behaviour (RSB). Data analysis included test of associations using Chi-square, independent t-test and repeated measures ANOVA. Predictors were identified using binary logistic regression. Results In the intervention group, there was a statistically significant main effect on mean knowledge score (F = 2117.252, p =  < 0.001) and mean attitude score (F = 148.493, p =  < 0.001) from T0 to T2 compared to the control group which showed no statistically significant main effects in knowledge (p = 0.073), attitude (p = 0.142) and RSB (p = 0.142). Though the mean RSB score declined from T0 to T2, this effect was not statistically significant (F = 0.558, p = 0.572). Post-intervention, being female was a positive predictor of good SRH knowledge; being male was a positive predictor of RSB while being in a higher-class level was a negative predictor of RSB. Conclusion The mHealth-based CSE was effective in improving SRH knowledge and attitude among in-school adolescents. This strategy should be strengthened to bridge the SRH knowledge and attitude gap among in-school adolescents. Trial registration Retrospectively registered on the Pan African Clinical Trial Registry (pactr.samrc.ac.za) on 19 October 2023. Identification number: PACTR202310485136014